Use of the Over-The-Scope Clip for treatment of refractory upper gastrointestinal bleeding: a case series - Chan, Shannon M.; Chiu, Philip W. Y.; Teoh, Anthony Y. B.; Lau, James Y. W. (Endoscopy, 2014)
The Over-The-Scope Clip (OTSC; Ovesco, Tübingen, Germany) is a novel endoscopic clipping device designed for tissue approximation. The device has been used in the closure of fistulas and perforations. We hereby report on a series of patients in whom OTSCs were used for endoscopic control of refractory or major upper gastrointestinal bleeding from lesions in the gastroduodenal tract between 1 July and 31 December 2012. Nine patients were included (median age 72.5 years, range 39 – 91) with bleeding gastric ulcers (n = 2), bleeding duodenal ulcers (n = 5), bleeding gastrointestinal stromal tumor in the stomach (n = 1), and bleeding from ulcerative carcinoma of the pancreas (n = 1). The median size of the ulcers was 2.5 cm (range 1 – 4). Six of the nine patients had undergone previous endoscopic hemostasis. Technical success was achieved in all patients and the clinical effectiveness was 77.8 %. The OTSC is a safe and effective method of endoscopic hemostasis for major bleeding from miscellaneous upper gastrointestinal causes and should be considered in patients with refractory bleeding after failure of conventional methods of endoscopic hemostasis.